FORMULASI DAN UJI EVALUASI SEDIAAN STICK BALSEM DARI MINYAK ATSIRI SERAI DAPUR (Cymbopogon citratus) SEBAGAI ANALGESIK DAN AROMATERAPI RELAKSAN - Rachman, Ellyza Audhina; Hutahaen, Titi Agni; Zuhriyah, Ainu (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2023)
Lemongrass essential oil (Cymbopogon citratus) has potential as a medicine because it contains chemical compounds citronellal, citronellol, geraniol which work as analgesics and aromatherapy. One of the pharmaceutical preparations that can be used for analgesic and aromatherapy is a stick balm preparation because it can treat mild scale pain and stress. The aim of this study was to analyze the chemical compounds in citronella essential oil using the GCMS tool, to formulate it as a stick balm which has a function as an analgesic and aromatherapy as well as to evaluate the preparation. The method in this study is true experimental laboratory. Lemongrass essential oil is formulated into 4 different preparations. The results of testing citronella essential oil using GCMS did not meet the expectations of the researchers because the results did not read the compound being sought. The results of the data read the chemical compound groups that are thought to have the same function as citronellal, citronellol, geraniol. Aldehydes and alcohols. Lemongrass essential oil can be formulated into 4 balm sticks with different concentrations. Evaluation test of stick balm organoleptic test, homogeneity test, pH test, adhesion test, spreadability test, analgesic test, aromatherapy test and irritation test. The results of all preparation evaluation tests have met Indonesian national standards.